Hanging on By a Thread: The Exclusionary Rule (Or What's Left of it) Lives for another Day - Moran, David A. (2011)
Back when there was a Soviet Union, foreign intelligence officers would anxiously await the May Day parade in Moscow to see who would be standing next to the chairman of the Communist Party and who would be missing from the reviewing platform altogether. Since the Soviet government and the statecontrolled press published very little about what was really going on in the halls of state power, this was considered the most reliable way to determine who was in or out of favor and, by extension, how the domestic and foreign policies of the world's second most powerful country were likely to change in the near term. Readers will, I hope, forgive me when I say that I feel a bit like those erstwhile Kremlinologists whenever I await a decision from the Supreme Court involving the Fourth Amendment exclusionary rule. Ever since the Court's 2006 decision in Hudson v. Michigan,' which I managed to lose by a 5-4 vote as Booker T. Hudson's attorney, it has been clear that there are four votes on the Court to overrule Mapp v. Ohio2 and thereby abolish the exclusionary sanction for Fourth Amendment violations. In Hudson, the majority held that the exclusionary rule would not apply to knock-and-announce violations at all and, in so holding, broadly suggested that the exclusionary rule itself was unjustifiable and outdated. The only thing apparently standing between Mapp and an outright abrogation of the exclusionary rule was Justice Kennedy, who signed the majority opinion in Hudson but then issued a cryptic concurrence seemingly repudiating the very same vehemently anti-exclusionary language in the majority opinion that he had joined. For three years after Hudson, the Court seemed determined to stay away from Fourth Amendment cases altogether. Perhaps this is because neither the majority justices nor the dissenters in Hudson knew where Justice Kennedy really stood as to the continuing vitality of the exclusionary rule.4 Finally, in 2009, the Court took a case, Herring v. United States,5 that gave the Court an opportunity to expand on Hudson. The nominal issue in Herring was whether evidence should be excluded when a police officer reasonably relied on an erroneous arrest warrant in a police database to justify an arrest and resulting search.6 In the resulting 5-4 decision concluding that such evidence should not be suppressed, clues emerged as to the internal struggle that must have been going on between Justice Kennedy and the others in the majority. Unlike Justice Scalia's anti-exclusionary jeremiad in Hudson, there is no language in Herring directly suggesting that Mapp should be overruled. Instead, the majority opinion by Chief Justice Roberts contained a different, more subtle attack on the exclusionary rule, by suggesting that exclusion may be available only to punish deliberate, reckless, or grossly negligent violations of the Fourth Amendment.' When the police violate the Fourth Amendment negligently (as opposed to grossly negligently ), the Herring majority suggested, the violation lacks sufficient culpability to justify the heavy sanction of exclusion. I use the word suggested in the preceding paragraph instead of held because the distinction the Herring majority drew between various culpable mental states that police officers might have while violating the Fourth Amendment is entirely unnecessary to the result. Since, according to the majority, the police acted reasonably in relying on a database of warrants that was well-maintained and relatively error-free,9 the case seemed to provide no occasion for the Court to distinguish between officers who are merely negligent and officers acting with more culpable mental states. On the contrary, the majority concluded that the police in Herring were not negligent at all. To put it simply, the language in Herring limiting the exclusionary rule to violations committed by grossly negligent (or worse) police officers looks like dicta. The four justices in dissent in Herring were careful not to refer to the culpability language in the majority opinion as a holding.'0 But would the majority view it as established law in a future case? It was with great interest and anxiety, therefore, that I awaited the Court's decision this summer in Davis v. United States,12 the second case since Hudson in which the exclusionary rule may have been in play. In Davis, the nominal issue was whether evidence should be excluded when the binding precedent the officers relied upon to perform a search was overruled after the search was performed.' 3 Given the Court's longstanding precedent holding that the sole purpose of the exclusionary rule is to deter the police from committing Fourth Amendment violations, the outcome in Davis was entirely predictable: the police won. Still, the case did present some interesting and knotty problems as to how to square the result with the Court's retroactivity jurisprudence. But more interesting than the result to me were two aspects of the majority opinion that tell us more about where the Court really stands on the exclusionary rule. First, the tone of Justice Alito's majority opinion in Davis was almost, but not quite, as critical of Mapp and the exclusionary rule as Justice Scalia's opinion in Hudson. Second, Justice Alito tried his best to elevate the Herring dicta to established precedent even though that dicta has no arguable application at all to the facts in Davis. In this term paper, therefore, I will do two things. First, I will discuss the facts and holding of Davis and explain why I concur with the outcome even though I agree with almost nothing else in Justice Alito's majority opinion. Second, I will use the clues sprinkled in that opinion to gauge (or guess?) where the Court really stands on the future of the exclusionary rule